2008
DOI: 10.1111/j.1471-0528.2007.01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in bone and reproductive health in adolescents with anorexia nervosa

Abstract: Anorexia nervosa (AN) initiates an adaptive response at the level of the hypothalamus, which results in a complex interplay involving most elements of the neuroendocrine axis. Consequences of onset of disease in adolescence include amenorrhoea, pubertal arrest with potential loss of target height, and osteoporosis with reduced capacity for future attainment of peak bone mass. With recovery, delay in restoration of menses is common. Hormonal therapies for restoration of bone mineral density (BMD) in adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 142 publications
(244 reference statements)
2
43
1
20
Order By: Relevance
“…Both men and women achieve peak bone mineral density (BMD) in their early twenties [22]. The peak BMD depends on genetic background (family history), caloric and calcium intake, normal hormonal levels during childhood and adolescence [23].…”
Section: ) Epidemiology Of Osteopenia and Osteoporosismentioning
confidence: 99%
“…Both men and women achieve peak bone mineral density (BMD) in their early twenties [22]. The peak BMD depends on genetic background (family history), caloric and calcium intake, normal hormonal levels during childhood and adolescence [23].…”
Section: ) Epidemiology Of Osteopenia and Osteoporosismentioning
confidence: 99%
“…Kronik enerji eksikliğinde, oreksijenik hormon olan ghrelin artar (31). Yapılan çalışmalarda, aşırı egzersiz yapmaya bağlı amenoresi olan genç kadın-ların ghrelin düzeyleri normalden %85 daha yüksek değerlerde saptanmıştır (32).…”
Section: üReme Hormonlarındaki Değişimunclassified
“…Eğer AN belirtileri ergenlik başladık-tan sonra ortaya çıkarsa, pubertal süreç uzar ve ikincil amenoreye neden olur (31).…”
Section: üReme Hormonlarındaki Değişimunclassified
“…Furthermore, this therapy should prevent the development of osteoporosis. Respect to oral estrogens, it has been demonstrated that transdermal hormone replacement therapy has better effects on bone density than oral hormone replacement therapy due to the absence of the first-pass hepatic metabolism (Jayasinghe et al, 2008). In addition, calcium and vitamin D supplementation is highly suggested (Master-Hunter & Heiman, 2006).…”
Section: Treatment Of Hypothalamic and Pituitary Disordersmentioning
confidence: 99%